2002
DOI: 10.1007/bf02410874
|View full text |Cite
|
Sign up to set email alerts
|

Computer aided photoelasticity by an optimum phase stepping method

Abstract: ABSTRACT--In this paper an automated photoelastic method based on the phase stepping technique is described. It provides full-field maps of the isoclinic parameter and the relative retardation. The technique is based on processing six images of a photoelastic specimen acquired using plane and circularly polarized light. The number of acquisitions and the type of polariscope used in this approach have been chosen with the aim at reducing the influence of quarter wave plate errors and obtaining raw photoelastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 19 publications
2
38
1
Order By: Relevance
“…Figure 6 shows the isochromatic fringes at the ROI and the section chosen for the measurement of the retardation. Figure 7 shows the retardation δ 0 along the measurement section determined by the RGB method (using both the calibration on polycarbonate and the self-calibration) and, for comparison, by the phase-shifting method based on six acquisitions [19]. Similar results are obtained by the simplified phaseshifting method based on three acquisitions [5] and with the phase-shifting method in white light [16].…”
Section: Methodsmentioning
confidence: 62%
“…Figure 6 shows the isochromatic fringes at the ROI and the section chosen for the measurement of the retardation. Figure 7 shows the retardation δ 0 along the measurement section determined by the RGB method (using both the calibration on polycarbonate and the self-calibration) and, for comparison, by the phase-shifting method based on six acquisitions [19]. Similar results are obtained by the simplified phaseshifting method based on three acquisitions [5] and with the phase-shifting method in white light [16].…”
Section: Methodsmentioning
confidence: 62%
“…Barone and Petrucci observed that for light fluctuations less than 10%, the classic error function (6) is applicable, while for higher fluctuations the authors propose the application of the chromatic coordinate r, g and b from Eq. (9)(10)(11). In order to reduce the localised fluctuations they also recommended the application of median filtering techniques to the R, G and B values (separately), in particular in the creation of the look-up table, as described in Section 2.1.…”
Section: Birefringent Coatingsmentioning
confidence: 99%
“…Because of the periodicity of the tangent function, the above maps are wrapped, it is therefore necessary to apply procedures of unwrapping. Various methods that minimize the influence of the error of quarter-wave plates on isochromatic and isoclines have been proposed [8,9]. For a survey on the phase shifting methods, the reader is referred to the literature [10].…”
Section: Introductionmentioning
confidence: 99%
“…In particular the analysed section is located at the fringe of order 1 in the tensile zone of the carrier. Figure 9(b) shows the retardation along the chosen section as determined by the relationship (16) and by using a six acquisitions phase shifting method [13] for comparison. Almost identical results are obtained by the simplified phase shifting method based on three acquisition [6] and with the phase shifting method in white light [14].…”
Section: The Following Light Sourcesmentioning
confidence: 99%